The use of Corpus in the writing activities among Omani ESL learners - Alabri, Naif Salim Khamis; Saad, Mohammad Azannee (Al-Kindi Center for Research and Development, 2025)
The use of corpus as a form of technology in language teaching and learning has received attention from a number of studies. Generally, corpus which refers to a collection of real texts is viewed as having a potential to assist language learners in many aspects such as vocabulary and writing. However, the effective techniques or strategies of using corpus have not been clear where issues including learners not knowing how to utilize corpus to benefit their language learning activity are evident. Inlight of this, the present study evaluates the impacts of Corpus on the writing performance of ESL learners and later explores the challenges experienced by them to incorporate corpus tools into their writing activity. Using the mixed-method research design, six (N = 6) participants who are Omani ESL learners at the Foundation Programme levelwere put in pre-and post-Corpus incorporated writing activities as well as interviewed for their experience using Corpus. Results showed that the learners made improvement in their writing evident through more complex vocabularies are employed and fewer grammatical mistakes. However, the participants reported a number of challenges that may cause the incorporation to be difficult. The findings are significant for future framework or model on how the use of corpus can be effectively incorporated into language teaching and learning.